Ellipsis as a Marker of Interaction in Spoken Discourse - White, Jonathan (Research in Language, 2013)
In this article, we discuss strategies for interaction in spoken discourse, focusing on ellipsis phenomena in English. The data comes from the VOICE corpus of English as a Lingua Franca, and we analyse education data in the form of seminar and workshop discussions, working group meetings, interviews and conversations. The functions ellipsis carries in the data are Intersubjectivity, where participants develop and maintain an understanding in discourse; Continuers, which are examples of back channel support; Correction, both self- and other-initiated; Repetition; and Comments, which are similar to Continuers but do not have a back channel support function. We see that the first of these, Intersubjectivity, is by far the most popular, followed by Repetitions and Comments. These results are explained as consequences of the nature of the texts themselves, as some are discussions of presentations and so can be expected to contain many Repetitions, for example. The speech event is also an important factor, as events with asymmetrical power relations like interviews do not contain so many Continuers. Our clear conclusion is that the use of ellipsis is a strong marker of interaction in spoken discourse.